Factors associated with final attempts during counterattacks in Champion League 2018-2019 matches - Armatas, Vasilis; Zacharakis, Emmanouil; Apostolidis, Nikolaos (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Although counterattacks are the most effective style of play for scoring goals, they occur less frequently during soccer matches than organized attacks and the research on the subject conducted to date is limited. Aim of Study. This study sought to investigate factors associated with final attempts during counterattacks in Champions League 2018- -2019 matches. Material and Methods. The sample included 1415 ball recoveries corresponding to 16 knock-out matches. Multidimensional qualitative data using 11 ordered categorical variables were obtained to characterize each counterattack. The data were analysed using chi-squared tests and binary logistic regression. Results. Bivariate analysis revealed that the performance indicators significantly associated with the final attempt in a counterattack included the defenders’ positions, invasive zone, number of passes, counterattack duration and zone of recovery. Spatial analysis revealed that final attempts from counterattacks were most frequently assisted from the central zone outside the box (Zone 7: 23%) and finishing was typically executed from the central zone inside the box (Zone 4: 30.4%). The regression model indicated significant probabilities of a final attempt when the ball was recovered inside the invasive zones, used a high proportion of penetrative passes and involved 4 or more attacking players. Conclusions. This study enhances coaches’ understanding of the factors that affect counterattack effectiveness and provide practical implications for developing and implementing training sessions for the transition phase.
Keywords: soccer; transition phase; effectiveness; goal scoring